Simulation-based Methodology to Investigate the Impact of Material Type and Compressive Speed Variation on Effective Strain Rate and Springback - Amrullah, Radhi Nurvian; Hadi, Syamsul; Rizza, Muhammad Akhlis (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
To obtain the desired results in the manufacturing process, especially the bending process, the occurrence of springback must be reduced. The effective strain rate must be increased to predict the increase in material. This study uses a simulation method to determine the influence of material type and compressive speed variation on spring back and effective strain rate. This study uses 3 kinds of materials: JIS SPHD, JIS A1100 BE, and JIS SN400A, and speed variations, namely: 90 mm/s, 105 mm/s, and 120 mm/s. This study shows that JIS SN400A material has the smallest springback value compared to JIS A1100 BE and JIS SPHD materials because the nitrogen content in JIS SN400A makes it more plastic. At a compressive speed of 105 mm/s, springbacks tend to decrease in JIS SN400A, JIS SPHD, and JIS A1100 BE materials caused by residual stress. The average effective strain in JIS SN400A material increases in line with the increase in compressive speed, because JIS SN400A material has the highest melting temperature compared to JIS SPHD and JIS A1100 BE materials to reduce the risk of residual stress, the nitrogen content in JIS SN400A material also plays a role in increasing the effective strain value.